Management of pancreatic lithiasis in a 5-year-old girl - Yalçin, Sule; Ciftçi, Arbay O; Simşek, Halis; Haliloğlu, Mithat; Sahin, Burhan; Senocak, M Emin (The Turkish Journal of Pediatrics, 2008)
Pancreatic lithiasis causing chronic pancreatitis is a very rare entity in childhood. A five-year-old girl presenting with pancreatic lithiasis was treated successfully with a well-organized diagnostic and therapeutic algorithm. The authors emphasize that early diagnosis followed by appropriate therapeutic pancreatographic procedures instead of primary invasive surgical approach can certainly ameliorate progressive and irreversible pancreatic damage. The clinicopathologic features of this rare entity are discussed, with emphasis on diagnosis and treatment.